Four Violins Ensemble as a tool for Violin Instrumental Teaching (Ex Chordis, 2023)
The daily practice of violin teaching suggests that playing music together in an ensemble can bring significant benefits. This is particularly evident when considering the experience of a quartet of unaccompanied violins, a formation historically linked to traditional teaching methods. Such training allows for establishing comparisons, analogies, and positive challenges among group members, regardless of their instrumental skills. The performance of a violin quartet involves musical and social interactions among the performers, making the musical performance a typically collective activity. This leads us to reflect on the theoretical foundations supporting the idea that collective practice can support individual practice and the benefits that can arise, such as independence in the musical field and the development of self-regulation. In this context, this paper aims to guide the reader through the main fields of collective teaching, including the self-regulation cycle in effective practices, the principles of cognitive apprenticeship and cooperative learning, and the positive role of peer learning in a music ensemble. The ultimate aim is to deepen, in the educational field, the connections between collective and individual practice, exploring the potential impact of the violin quartet on individual violin practice.
Keywords: Violin Ensemble; Self-Regulation; Cognitive Apprenticeship; Cooperative Learning; Peer Learning; Chamber Music